In Situ Nucleation‐Decoupled and Site‐Specific Incorporation of Å‐Scale Pores in Graphene Via Epoxidation (Adv. Mater. 51/2022). Issue 51 (22nd December 2022) - Huang, Shiqi; Villalobos, Luis Francisco; Li, Shaoxian; Vahdat, Mohammad Tohidi; Chi, Heng‐Yu; Hsu, Kuang‐Jung; Bondaz, Luc; Boureau, Victor; Marzari, Nicola; Agrawal, Kumar Varoon
Abstract : Graphene Nanopores In article number 2206627, Kumar Varoon Agrawal and co‐workers describe how ångstrom‐scale pores are generated in graphene at a desired site, on demand, by controlled gasification of pre‐formed epoxy clusters. This strategy allows independent control of pore density and pore size. The illustration shows CO2 released from the gasification event.